Find the product mentally.
(z - 12)(z + 12)
z2 - 144
z2 - 24z - 144
z2 + 144

(z - 12)(z + 12) = z^2 - 144

s

Question

Asked 6/24/2016 10:30:07 AM

Updated 6/24/2016 10:47:32 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/24/2016 10:47:32 AM]

Rating

There are no new answers.

Evaluate (x + y ) 0 for x = –3 and y = 5.
–
0
1
2

Question

Updated 6/22/2016 11:20:11 AM

1 Answer/Comment

Evaluate (x + y ) 0 for x = –3 and y = 5.

(-3 + 5 )^0

= 2^0

= 1

(-3 + 5 )^0

= 2^0

= 1

Added 6/22/2016 11:20:07 AM

This answer has been confirmed as correct and helpful.

Rock layers are placed under compressional stress: reverse faultnormal faultstrike-slip fault

Question

Updated 2/1/2019 3:52:10 PM

1 Answer/Comment

Click on the expression until you find the right quotient.
36m 5 n 5 ÷ (12m 3)
**Weegy:** 36m^5 n^5 / (12m^3) = 3m^2 n^5 **User:** Click on the expression until you find the right quotient.
12x a y b ÷ (-6x a y)
(More)

Question

Updated 6/27/2016 9:56:11 AM

1 Answer/Comment

12xayb ÷ (-6xay)

= -12b/6

= -2b

= -12b/6

= -2b

Added 6/27/2016 9:56:11 AM

This answer has been confirmed as correct and helpful.

Evaluate the following expression.
(-6)-2
-36
-1/36
1/36
36 **Weegy:** (-6)^-2 = 1/(-6)^2 = 1/36 (More)

Question

Updated 6/23/2016 10:21:11 AM

0 Answers/Comments

33,162,271

questions answered

There are no comments.